Impact of FLDs on the knowledge level of mustard production technology and yield between beneficiary and non-beneficiary farmers: IMPACT OF FLDs ON MUSTARD BETWEEN BENEFICIARY AND NON-BENEFICIARY FARMERS - S R MEENA; G S BANGARVA; I M KHAN (Journal of Oilseeds Research, 2019)
Indian mustard is an important rabi oilseed crop of India. Rajasthan is the leading producer of the crop. In order to enhance the productivity of the crop, the KVKs and DRMR have conducted the frontline demonstrations with recommended package of practices. The impact of the FLDs in terms of increase in knowledge level of farmers and the yields were assessed in this study. The study was conducted in Bharatpur division and the results indicated higher knowledge scores and higher yieldsscores ofthe beneficiary farmers as compared to non-beneficiary farmers indicating the impact of conduct of FLDs in the region.